New insights into HCV-related rheumatologic disorders: A review - Cacoub, Patrice (J Adv Res, 2017)
Hepatitis C virus (HCV) infected patients are known to be exposed to major liver complications i.e. cirrhosis and hepatocellular carcinoma. In addition, many extrahepatic manifestations including rheumatologic disorders have been reported in up to two-third of HCV infected patients. These manifestations include frank auto-immune and rheumatic diseases (such as arthralgia, myalgia, arthritis, sicca syndrome and vasculitis) which may dominate the course of infection. Until recently, the standard of care of HCV has been the use of interferon-alpha based regimens, which not only had limited effectiveness in HCV cure but were poorly tolerated. In patients with rheumatic diseases interferon-based regimens may be problematic given their association with a wide variety of autoimmune toxicities. Recent therapeutic advances with new direct anti-HCV therapies (interferon-free) which are more effective and better tolerated, make screening for this comorbidity in patients with rheumatic disorders more important than ever. This review aimed to outline main HCV extrahepatic with a special focus on rheumatologic manifestations.